2011
DOI: 10.1371/journal.pone.0016646
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Exerts Age-Dependent Effects on Behavior and Amygdala Neuroplasticity in the Rat

Abstract: The selective serotonin reuptake inhibitor (SSRI) Prozac® (fluoxetine) is the only registered antidepressant to treat depression in children and adolescents. Yet, while the safety of SSRIs has been well established in adults, serotonin exerts neurotrophic actions in the developing brain and thereby may have harmful effects in adolescents. Here we treated adolescent and adult rats chronically with fluoxetine (12 mg/kg) at postnatal day (PND) 25 to 46 and from PND 67 to 88, respectively, and tested the animals 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 66 publications
(79 reference statements)
3
65
2
Order By: Relevance
“…However, since we did not measure drug plasma concentrations we cannot be certain that differences in plasma concentrations underlie the different findings in the three experiments: "only" a treatment effect on behavioral studies and phMRI, whereas an interacting effect of age and treatment on the binding assays. In line with this, at higher oral concentrations of 12 mg/kg fluoxetine age-related treatment effects have been noted on behavior (Homberg et al 2011).…”
Section: Discussionsupporting
confidence: 71%
“…However, since we did not measure drug plasma concentrations we cannot be certain that differences in plasma concentrations underlie the different findings in the three experiments: "only" a treatment effect on behavioral studies and phMRI, whereas an interacting effect of age and treatment on the binding assays. In line with this, at higher oral concentrations of 12 mg/kg fluoxetine age-related treatment effects have been noted on behavior (Homberg et al 2011).…”
Section: Discussionsupporting
confidence: 71%
“…Flx administered orally is detected in the blood plasma of the animal [42]. The ability of SSRIs, in particular Flx, to cross the placental barrier is similar in humans and animals [rats: [18]; mice: [23]; sheep: [43]].…”
Section: Animals and Methodsmentioning
confidence: 99%
“…57 In the postischemic brain, selective serotonin reuptake inhibitors are neuroprotective through their anti-inflammatory effects and improve ischemia-induced spatial cognitive deficits by promoting hippocampal neurogenesis in the rat. 58 A clinical study, fluoxetine for motor recovery after acute ischemic stroke (FLAME), demonstrated in a larger cohort of patients (nϭ118) with moderate to severe hemiplegia after ischemic stroke that physiotherapy in combination with early treatment with fluoxetine enhances motor recovery and reduces the number of dependent patients compared with physiotherapy alone. 59 These interesting results call for even larger and more comprehensive trials with an extended focus on functional outcome parameters.…”
Section: Fluoxetinementioning
confidence: 99%